2004
DOI: 10.1536/jhj.45.205
|View full text |Cite
|
Sign up to set email alerts
|

Is the Beneficial Effect of Preinfarction Angina Related to an Immune Response?

Abstract: SUMMARYImmune-mediated mechanisms are thought to play a key role in the development of coronary artery disease and its thrombotic complications. Preinfarction angina has been suggested to improve left ventricular function and short-term outcomes.The purpose of the present study was to investigate the relation between the immune response and in-hospital clinical course in preinfarction angina.We prospectively evaluated 93 patients. Forty-three patients exhibited preinfarction angina within 24 hours before the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In patients, ischemic preconditioning, as indicated by preinfarction angina within 24 h before infarction, reduces infarct size and left ventricular remodeling, thereby potentially improving the prognosis of patients with an acute myocardial infarction (Anzai et al, 1995;Kloner et al, 1995;Kloner et al, 1998b;Papadopoulos et al, 2003;Yellon and Downey, 2003;Solomon et al, 2004;Tokac et al, 2004). When preinfarction angina occurred within 48 h before acute myocardial infarction, no such difference in irreversible tissue injury and outcome was measured compared with patients without any ischemic symptoms before infarction (Psychari et al, 2004).…”
Section: E Aging and Cardioprotectionmentioning
confidence: 99%
“…In patients, ischemic preconditioning, as indicated by preinfarction angina within 24 h before infarction, reduces infarct size and left ventricular remodeling, thereby potentially improving the prognosis of patients with an acute myocardial infarction (Anzai et al, 1995;Kloner et al, 1995;Kloner et al, 1998b;Papadopoulos et al, 2003;Yellon and Downey, 2003;Solomon et al, 2004;Tokac et al, 2004). When preinfarction angina occurred within 48 h before acute myocardial infarction, no such difference in irreversible tissue injury and outcome was measured compared with patients without any ischemic symptoms before infarction (Psychari et al, 2004).…”
Section: E Aging and Cardioprotectionmentioning
confidence: 99%
“…It was concluded that the level of IgE significantly increased during the acute phase of acute coronary syndromes and gradually decreased, supporting the role of acute inflammatory response and mast cell involvement in plaque rupture. 5 The incidence of complications (heart failure, recurrent angina, arrhythmia and coronary interventions) and in-hospital mortality were prospectively assessed in two study groups [9] consisting of 43 patients with preinfarction angina, within 24 h before the onset of acute myocardial infarction (preinfarction angina group), and 50 patients without preinfarction angina (sudden onset group). White blood cells and CRP were significantly lower in the preinfarction angina group than in the sudden onset group.…”
mentioning
confidence: 99%
“…Criqui et al (1987) reported the first results in a population-based study showing a significant positive association between total IgE levels and cardiovascular diseases (i.e., previous myocardial infarction, stroke, and noninvasively diagnosed large-vessel peripheral arterial disease) in males [15]. Subsequent cross-sectional studies reported increased total IgE levels in patients with AMI, coronary heart disease, and angina compared with healthy counterparts or controls [8,9,10,16]. Using the same data from NHANES 2005–2006 as in the present study, Shiue et al (2013) investigated the effect of total serum and 19 allergen-specific IgE levels with regard to self-reported cardiovascular events, including coronary heart disease, stroke, heart failure, heart attack, and angina [14].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanism is both IgE-independent and -dependent, and involves mast cells that trigger the release of vasoactive inflammation mediators, contributing to the development and progression of myocardial ischemia and thrombosis [5,6,7]. Several cross-sectional studies have demonstrated elevated total serum IgE levels in patients with acute myocardial infarction (AMI), sudden cardiac arrest, and coronary artery disease [8,9,10]. A few prospective studies have suggested elevated total IgE levels as an independent marker of AMI development [11,12].…”
Section: Introductionmentioning
confidence: 99%